Salivary cortisol in Schizophrenia: a selective review and meta-analysis of controlled studies of the past decade - Walter Paganin; Sabrina Signorini (Biomarkers in Neuropsychiatry)
Background: Stress and trauma significantly contribute to various psychiatric disorders, including schizophrenia. Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, particularly abnormal cortisol secretion, is implicated in schizophrenia's pathophysiology. Salivary cortisol, a convenient measure, provides insights into HPA axis activity. This systematic review and meta-analysis assess salivary cortisol levels in individuals with schizophrenia compared to healthy controls, evaluating its potential as a biomarker for schizophrenia. Aim: To assess the differences in salivary cortisol levels at baseline and in response to stress between patients with schizophrenia and healthy controls, determining the reliability of salivary cortisol as a biomarker for schizophrenia. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines. We searched MEDLINE/PubMed, Cochrane Central, and EMBASE for human studies on schizophrenia and controls published from January 1, 2013, to July 1, 2023, reporting baseline or post-stress salivary cortisol levels. Exclusions were non-human studies, non-specific schizophrenia diagnoses, or missing cortisol data. Two reviewers independently extracted data and appraised quality, resolving discrepancies by consensus. Due to significant heterogeneity (I² = 94 % for baseline, 75 % for stress response), a random effects model was used. Results: Nineteen studies were initially selected, with twelve excluded due to non-specific schizophrenia diagnoses and missing cortisol data. The final meta-analysis included seven studies with 507 schizophrenia patients and 175 healthy controls. Key findings include: Baseline cortisol levels: No significant difference in baseline salivary cortisol levels between schizophrenia patients and healthy controls (pooled estimate: −0.02, 95 % CI: −0.47–0.42). Cortisol response to stress: No significant difference in post-stress cortisol levels between the two groups (pooled estimate: 0.03, 95 % CI: −1.84–1.79). Study variability: High variability across studies due to differences in design, patient characteristics, and cortisol measurement techniques. Despite some evidence of altered cortisol dynamics in schizophrenia, high variability in methodologies and confounding factors like medication use and psychosocial stressors complicate definitive conclusions. Conclusion: The review underscores the potential of cortisol as a biomarker for stress response; however, its use in diagnosing schizophrenia remains inconclusive. Individual variability and methodological differences limit the diagnostic accuracy of salivary cortisol. Future research with larger sample sizes, uniform methodologies, and comprehensive control for confounding variables is essential to elucidate the role of salivary cortisol in schizophrenia and its potential clinical applications.